Fermentation performance, nutrient composition, and flavor volatiles in soy milk after mixed culture fermentation. (October 2022) - Peng, Xinhui; Liao, Yi; Ren, Kunyu; Liu, Yanwei; Wang, Mengmeng; Yu, Aihua; Tian, Tian; Liao, Peilong; Huang, Zhaoxian; Wang, Huan; Jiang, Lianzhou
Abstract: In this study, a mixed culture of lactic acid bacteria (LAB) and kombucha bacteria was used to ferment soy milk. The microbial composition and the rheological properties, isoflavones, vitamins, and volatile flavor substances were quantitatively analyzed during fermentation. The fermentation process could significantly change the viscoelastic rheological properties of soy milk. Most of the isoflavone glycosides were hydrolyzed to aglycones by β-glucosidase produced during fermentation. The isoflavone content increased significantly as fermentation progressed. B vitamins content increased significantly, riboflavin content increased from 117.44 to 162.58 µg/g dry weight (dw), and cobalamin content, not detected before fermentation, increased to 106.73 µg/g dw. Microbial fermentation promoted protein aggregation and decreased the fat content of soy milk. After fermentation, the content of characteristic flavor substances in soybean, such as hexanal, was significantly reduced, and some new flavor compounds were generated from the fermentation-derived alcohols, esters, and acids. The combination of LAB and kombucha bacteria can enrich the taste and significantly enhance the nutritional properties and antioxidant capacity of fermented soy milk and provides a new idea for the research and development of fermented soy milk and its related plant-based fermented products. Graphical Abstract: ga1 Highlights: Indirect ventilation cultures allow bacteria and fungi to grow well. Mixed fermentation can increase the amount of soy isoflavones and vitamins. Mixed fermentation can reduce the beany smell and produce new flavors.